How Reyog Dadak Lar Pitik Can Induce Rain? A Study on the Mysticism of the Customary Ceremony for Rain Invocation - Hayyun Lathifaty Yasri; Ulfi Andrian Sari; Azharotunnafi; Ratna Nulinnaja; Ali Nasith (NAJAHA, 2025)
Reyog Dadak Lar Pitik in Sidowayah Village, Krebet District, Ponorogo Regency is a form of local adaptation of the Ponorogo Reyog art, which is adapted to the socio-economic conditions of the local community. Limited access to primary materials such as peacock feathers and tiger skins has encouraged the community to utilise chicken feathers, which are abundantly available in the region, as the primary raw material. More than just an artistic performance, Reyog Dadak Lar Pitik is an important element in traditional rain-seeking rituals that are steeped in mystical values, unlike other Reyog variants. This study aims to uncover the mystical dimensions contained in the history of the birth of the belief that Reyog Dadak Lar Pitik can bring rain and its performances in traditional rain-seeking ceremonies, both before, during, and after the performance. The approach used is a qualitative approach with a phenomenological method. The theoretical framework used includes Max Weber's theory of charisma and spiritual leadership as well as Claude Lévi-Strauss's structuralist theory. Informants in this study consisted of the village head, the head of the Reyog Dadak Lar Pitik association, and several members of the association. The research results indicate mystical practices through a series of rituals such as genduri (gathering), the presentation of offerings as a symbol of a request for safety, the assignment of a specific jathil role to men, and the performance of lampah dodok (a kind of ritual offering) and offerings in the cemetery area as a form of respect for ancestors and spiritual powers. This study faces limitations due to the researchers' limited direct observation of the rituals, as the community performed the ceremonies only during periods of prolonged drought.